Cortical plasticity is preserved in nondemented older individuals with severe ischemic small vessel disease. Issue 6 (14th February 2012) - List, Jonathan; Duning, Thomas; Kürten, Julia; Deppe, Michael; Wilbers, Eike; Flöel, Agnes
Abstract: Ischemic small vessel disease (SVD) is a common finding on routine scans in older people, but cognitive sequelae vary considerably. To improve understanding of mechanisms underlying decline or preservation of cognitive function in this condition, we assessed cognition and cortical plasticity in 20 elderly subjects with severe SVD and 20 age‐matched controls without SVD, as rated on conventional MRI. Cognitive status was determined with a neuropsychological test battery, cortical plasticity induced with a paired associative stimulation protocol. Microstructural white matter changes were further analyzed for fractional anisotrophy using diffusion tensor imaging. We found that cortical plasticity as well as memory functions were preserved in severe SVD, while executive functions showed trendwise or significant decreases. Within the SVD group, lower white matter integrity in parahippocampal regions and posterior parts of the corpus callosum was associated with larger cortical plasticity, an association not seen for prefrontal white matter tracts. Enhanced cortical plasticity in subjects with lower white matter integrity in memory‐relevant areas might thus indicate a compensatory mechanism to counteract memory decline in severe SVD. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.